The Effect of the Alternative Prey, Paramecium caudatum (Peniculida: Parameciidae), on the Predation of Culex pipiens (Diptera: Culicidae) by the Copepods Macrocyclops albidus and Megacyclops viridis (Cyclopoida: Cyclopidae). Issue 1 (12th September 2018) - Cuthbert, Ross N; Callaghan, Amanda; Dick, Jaimie T A
Abstract: Biological control can be an effective tool to combat public health risks associated with mosquito-borne disease. However, target impacts of biological control agents may be reduced by biotic contexts such as the presence of alternative prey. In turn, this can impede our ability to realistically assess biocontrol agent efficacy. Here, we examine the effects of alternative ciliate prey on the predation potential of two cyclopoid copepods, Macrocyclops albidus Jurine (Cyclopoida: Cyclopidae) and Megacyclops viridis Jurine (Cyclopoida: Cyclopidae), toward larvae of the West Nile virus vector mosquito Culex pipiens Linnaeus (Diptera: Culicidae). Using functional responses (FRs; resource use under different resource densities), we demonstrate that both copepods exhibit potentially destabilizing type II FRs toward mosquito prey. However, where the alternative prey was present, we observed species-specific modulations to FR form and magnitude. For M. albidus, FRs remained type II where ciliate prey were present, however, maximum feeding rates on mosquito larvae were reduced. Conversely, for M. viridis, FRs moved toward more stabilizing type III, while maximum feeding rates on mosquito larvae were not significantly reduced. While both species of cyclopoid copepod were able to effectively target and consume larval mosquitoes in the presence of alternative prey, we demonstrate that overall efficacies may be reduced in aquatic habitats which contain multiple prey types. We thus advocate that biotic contexts such as prey selectivity should be integrated into predatory biocontrol agent examinations for mosquitoes which vector pathogens and parasites, to more holistically assess their efficacy.